Digital economy and information society scope and approach of legal regulation - Dukić-Mijatović Marijana; Mirković Predrag (Ekonomija: teorija i praksa, 2022)
The dynamic development of the global economy and trade is additionally connected with the exponential development of digital technologies. The progressive development of information technologies, as a segment of the information society, has influenced the changes in the traditional ways of performing economic activities. Global trends in the digital economy, which has equal importance in the domestic and foreign economic markets, require that countries adapt their legislation to the needs of the new way of functioning of the economy and economic relations in general. When it comes to digital economy, it is viewed on a par with the information society. The necessity of the existence and development of the digital economy is cohesively connected with the state of the information society in one economic space. In this domain, the digital economy relies on the degree of development of the information society of a market, since its progressive development is previously determined by the degree of development of the information society itself. Today, this parallel has been scientifically and professionally verified, and the development of the digital economy of a society is interdependent with the development of the information society. Given that this is a socio-economic phenomenon, the level of development of the information society, and consequently the digital economy, is in one segment pre-determined by the legislative framework governing the area. The subject of the research is the analysis of relevant issues in the context of the connection between the digital economy and the information society on the one hand and the legislative framework that regulates particular issues of interest in this area. The aim of the research is to define the application of the approach to the legal regulation of relevant issues in the field of digital economy from the aspect of the internal law of the Republic of Serbia.